NOISE AND ITS INFLUENCE ON HUMAN HEALTH - Stankov, Suncica; Stepančev, Bogdan (Medicinski časopis, 2022)
Noise pollution can affect human health and had an influence on daily life on people. As unpleasant sound, noise is defined as unwanted sound which can caused auditory and non-auditory effects on the human health. Except the exposure of noise in the workplace and it’s consecutive effects, noise as an exogenous stressor in everyday life had a different potential negative impact on human health, temporary or permanent. Occupational noise exposure mostly causes hearing loss and tinnitus among workers. The potential negative health effects of noise pollution include psychological distress, sleep disturbances, higher incidence of arterial hypertension and cardiovascular diseases. Also, noise exposure may be associated with an increased incidence of diabetes mellitus, headache and pulmonary diseases, with possible effects of noise in health centers and hospitals on medical staff and patients. Noise pollution can have specific negative influence on sensitive humans, as autistic and elderly people. Implementation of the different strategy and educational programs can reduce potential negative noise effects on human health.
Keywords: noise, risk factors, human health